RELIGIUSITAS MAHASANTRI SEMARANG - Kasan - Bisri; Nor - Khusomah (IAIN Kendari, 2019)
It is undeniably that religiosity is a dimension increasingly studied by researchers in psychology throughout the world. It is due to that religiosity is interesting phenomena which never ends to be discussed and investigated. One of them is religiosity of mahasantri community. This article aims to investigate religiousity of two mahasantri communities; mahasantri of Dafa Besongo and Ma’had al-Jamiah Walisongo. Through qualitative approach, there are mainly research findings. First, the religiousity of those two communities has similarities and differences which could be seen in every dimensions of religiousity. Second, influencing factors of their religiousity could be identified into two; internal and external. Internal fartor consists of knowledge and understanding degree and inner condition of subject. Meanwhile, external factor includes environmental circumstances, rules of pesantren, and figure of kyai.